IMPLEMENTASI SUPERVISI PENDIDIKAN PADA MASA PANDEMI COVID-19 DI MADRASAH ALIYAH SUNAN PRAWOTO PATI - Afif Takhlishi (Intelegensia : Jurnal Pendidikan Islam, 2018)
Education supervision in madrasah is carried out by the madrasah principal who acts as a supervisor. The madrasah principal must be able to carry out supervision activities to improve teacher performance. Supervision will be useful to identify deficiencies in the learning process carried out by teachers so far. Then look for solutions together to improve learning activities in class. This study reveals the supervision activities carried out by the principal of MA Sunan Prawoto on teacher's performance during the Covid-19 pandemic. The results of this study are: 1) Supervision is carried out through several stages, namely: planning, implementation, and follow up. Supervision is carried out by  madrasah principal and assisted by senior teachers. The things that are supervised include: administrative and academic supervision. Administrative supervision is carried out before the implementation of online class, while Academic supervision is carried out by means of supervisor joining virtual classes or online classes; 2) Obstacles in the implementation of supervision include: a) the tight schedule of the principal activities, b) the low IT skills of some educators, c) insufficient supporting facilities and infrastructure for online class; 3) The follow up taken in overcoming some teachers' mastery of teaching methods is by facilitated teachers to take online training through RUANG GURU application. Furthermore, madrasah also provide the facilities needed by these teachers in implementing online class in the form of the availability of adequate computers and gadgets.Keywords: Teacher; Madrasah Principal; Supervision